Oral supplementation of β-carotene benefits the hepatic structure and metabolism in mice (Mus musculus) exposed to a chronic ethanol consumption - Sandoval, Cristian; Vásquez, Bélgica; Vasconcellos, Adriana; Souza-Mello, Vanessa; Adeli, Khosrow; Mandarim-de-Lacerda, Carlos; del Sol, Mariano (Penerbit Universiti Kebangsaan Malaysia, 2022)
Ethanol cannot be excreted and must be metabolized in the liver. Alcoholic liver disease is a blanket term for conditions related specifically to the liver and alcohol use. The study aimed to evaluate the metabolic, biochemical and histological effects of the oral supplementation with β-carotene on the liver of C57BL/6 mice exposed to ethanol consumption. Thirty male C57BL/6 mice (Mus musculus) were divided into six experimental groups: Control (C), Low-dose alcohol (LA), Moderate-dose alcohol (MA), β-carotene (B), Low-dose alcohol+β-carotene (LA+B) and Moderate-dose alcohol+β-carotene (MA+B) group. One-way ANOVA was used. The greatest intake of calories was noted in the LA (65.4 ± 12.5 kJ) and MA (68.6 ± 18.6 kJ) groups. The LA+B and MA+B groups shown an improvement in the HOMA-IR index (8.7 ± 2.4 and 6.7 ± 3.5, respectively), increased ADH levels (16.2 ± 1.6 and 18.9 ± 0.5 pmol/minmL-1, respectively) and decreased insulin levels (14.0 ± 3.3 and 10.6 ± 5.7 μUmL-1, respectively). It was also observed that oral supplementation with β-carotene improved the hepatic parenchyma in the LA+B group, showing normal-sized hepatocytes, whereas in the MA+B group it relieved the structural damage, revealing fewer lipid droplets than the MA group.